2017
DOI: 10.1186/s12906-017-2039-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acupuncture on Lipopolysaccharide-induced anxiety-like behavioral changes: involvement of serotonin system in dorsal Raphe nucleus

Abstract: BackgroundAcupuncture has been used as a common therapeutic tool in many disorders including anxiety and depression. Serotonin transporter (SERT) plays an important role in the pathology of anxiety and other mood disorders. The aim of this study was to evaluate the effects of acupuncture on lipopolysaccharide (LPS)-induced anxiety-like behaviors and SERT in the dorsal raphe nuclei (DRN).MethodsRats were given acupuncture at ST41 (Jiexi), LI11 (Quchi) or SI3 (Houxi) acupoint in LPS-treated rats. Anxiety-like be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…Acupuncture is widely used to treat psychological problems such as anxiety and depression, and in many tests shows that acupuncture rarely gives serious side effects [20]. Acupuncture can work by regulating the level of inflammatory cytokines produced by lipopolysaccharide (LPS) by inducing inflammatory cytokines (tumor necrosis factor (TNF) α, interleukin (IL) -1β, IL-6) which can trigger depression or anxiety behavior [21]. Research conducted by Yue, et al showed that Electroacupuncture (EA) significantly reversed the increase induced Chronic Unpredictable Stress (CUS) on P2X7, Iba-1, IL-18 receptors, TNFα, and IL-6 expression and concluded that EA show antidepressant effects and reduce inflammation of the hippocampal nerve [22].…”
Section: Resultsmentioning
confidence: 99%
“…Acupuncture is widely used to treat psychological problems such as anxiety and depression, and in many tests shows that acupuncture rarely gives serious side effects [20]. Acupuncture can work by regulating the level of inflammatory cytokines produced by lipopolysaccharide (LPS) by inducing inflammatory cytokines (tumor necrosis factor (TNF) α, interleukin (IL) -1β, IL-6) which can trigger depression or anxiety behavior [21]. Research conducted by Yue, et al showed that Electroacupuncture (EA) significantly reversed the increase induced Chronic Unpredictable Stress (CUS) on P2X7, Iba-1, IL-18 receptors, TNFα, and IL-6 expression and concluded that EA show antidepressant effects and reduce inflammation of the hippocampal nerve [22].…”
Section: Resultsmentioning
confidence: 99%
“…The results of our behavioral investigations indicated anxiolytic-like effects of GPS in an animal model of anxiety. Administration of GPS after LPS injection significantly reduced anxiety-like behaviors in the EPM test, as indicated by increased exploratory behaviors, and more entries into the open arms (Yang et al 2017 ). Administration of GPS after LPS injection also significantly increased the number of central zone crossings in the OFT (Yang et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Administration of GPS after LPS injection significantly reduced anxiety-like behaviors in the EPM test, as indicated by increased exploratory behaviors, and more entries into the open arms (Yang et al 2017 ). Administration of GPS after LPS injection also significantly increased the number of central zone crossings in the OFT (Yang et al 2017 ). Therefore, because behaviors in the EPM test and OFT are related to LPS-related psychological symptoms, our results suggest that GPS may inhibit neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations